1992
DOI: 10.1083/jcb.117.5.1041
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for p34cdc2 kinase is restricted to mitosis in the mammalian cdc2 mutant FT210

Abstract: Abstract. The mouse FT210 cell line is a temperature-sensitive cdc2 mutant. FT210 cells are found to arrest specifically in G2 phase and unlike many alleles of cdc2 and cdc28 mutants of yeasts, loss of p34 '~c2 at the nonpermissive temperature has no apparent effect on cell cycle progression through the G1 and S phases of the division cycle. FT210 cells and the parent wildtype FM3A cell line each possess at least three distinct histone HI kinases. HI kinase activities in chromatography fractions were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 97 publications
(138 reference statements)
4
34
0
Order By: Relevance
“…Recent evidence, however, has shown that cyclin A activates both the mitotic cdc2 kinase and the related cdk2 kinase that is required for transition of cells into S phase (Fang and Newport, 1991;Pagano et al, 1992). To establish beyond doubt that inhibition was mediated via the mitotic kinase, we took advantage of the recent identification of a murine cell-line (FT210) with a temperature-sensitive lesion in cdc2 kinase activity (Th'ng et al, 1990;Hamaguchi et al, 1992). Decline of cdc2, but not cdk2, activity occurs rapidly both in vivo and in vitro upon shifting from 32 to 39°C (Th'ng et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence, however, has shown that cyclin A activates both the mitotic cdc2 kinase and the related cdk2 kinase that is required for transition of cells into S phase (Fang and Newport, 1991;Pagano et al, 1992). To establish beyond doubt that inhibition was mediated via the mitotic kinase, we took advantage of the recent identification of a murine cell-line (FT210) with a temperature-sensitive lesion in cdc2 kinase activity (Th'ng et al, 1990;Hamaguchi et al, 1992). Decline of cdc2, but not cdk2, activity occurs rapidly both in vivo and in vitro upon shifting from 32 to 39°C (Th'ng et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitation of histone kinases from cyclin-activated extracts followed the methods described by Hamaguchi et al (1992). Cyclin-activated or control cytosol (200 Mig) in KEHM buffer (200 Ml) was incubated with anti-cyclin A or anti-cyclin B sera (1 MAl) for 2 h at 4°C.…”
Section: Antibodiesmentioning
confidence: 99%
“…Entry into both S and M phase is controlled by cyclin-dependent kinases. Specialized cyclins and cdc2-1ike kinases control either the G1/S or the Gz/M transition in higher eukaryotes (Fang and Newport 1991;Hamaguchi et al 1992; Baldin et al 1993;Knoblich and Lehner 1993;Quelle et al 1993;Stem et al 1993; van den Heuwel et al. 1993;Knoblich et al 1994; for review, see Sherr 1993; Solomon 1993).…”
mentioning
confidence: 99%
“…Binding of growth-regulatory ligands results in the activation of signaling pathways that trigger direct alteration of specific metabolic pathways as well as immediate and delayed changes in gene expression (65). Mitogenic stimulation initiates a program of sequential synthesis of proteins, termed cyclins, that complex with and activate cyclin-dependent kinases (cdks) (9, 29-31, 39, 52, 54, 64, 67), enzymes that modulate key regulatory events leading to progression through and transitions between different stages of the cell cycle (7,13,20,21,47,55,64). The order of cyclin synthesis during cell cycle traverse has been examined in a variety of cells, including T cells, macrophages, epithelial cells, and fibroblasts (16,30,31,44,45,50,52).…”
mentioning
confidence: 99%